Building responsive supervision over smaller banks in Europe: an insight from the Principal-Agent perspective. Issue 3 (3rd July 2019) - Gren, Jakub
Abstract: The Single Supervisory Mechanism (SSM) is an administrative arrangement of national assistance to the ECB in exercising its exclusive supervisory competence. It sets two systems of assistance: ECB Direct Supervision (for large banks) and Indirect Supervision (for smaller and medium-sized banks) supervision. This paper analyzes dynamics between the ECB Banking Supervision as the principal and NCAs as its agents in the system of ECB Indirect Supervision. It identifies six formal (statutory) accountability and control mechanisms which are put at the ECB's disposal to monitor the way how the NCAs carry SSM supervisory tasks when exercising the ECB's exclusive supervisory competences under the SSM Regulation.